Using homology modeling to interrogate binding affinity in neutralization of ricin toxin by a family of single domain antibodies. Issue 11 (4th August 2017) - Bazzoli, Andrea; Vance, David J.; Rudolph, Michael J.; Rong, Yinghui; Angalakurthi, Siva Krishna; Toth, Ronald T.; Middaugh, C. Russell; Volkin, David B.; Weis, David D.; Karanicolas, John; Mantis, Nicholas J.
Abstract: In this report we investigated, within a group of closely related single domain camelid antibodies (VH Hs), the relationship between binding affinity and neutralizing activity as it pertains to ricin, a fast‐acting toxin and biothreat agent. The V1C7‐like VH Hs (V1C7, V2B9, V2E8, and V5C1) are similar in amino acid sequence, but differ in their binding affinities and toxin‐neutralizing activities. Using the X‐ray crystal structure of V1C7 in complex with ricin's enzymatic subunit (RTA) as a template, Rosetta‐based homology modeling coupled with energetic decomposition led us to predict that a single pairwise interaction between Arg29 on V5C1 and Glu67 on RTA was responsible for the difference in ricin toxin binding affinity between V1C7, a weak neutralizer, and V5C1, a moderate neutralizer. This prediction was borne out experimentally: substitution of Arg for Gly at position 29 enhanced V1C7's binding affinity for ricin, whereas the reverse (ie, Gly for Arg at position 29) diminished V5C1's binding affinity by >10 fold. As expected, the V5C1R29G mutant was largely devoid of toxin‐neutralizing activity (TNA). However, the TNA of the V1C7G29R mutant was not correspondingly improved, indicating that in the V1C7 family binding affinity alone does not account for differences in antibody function. V1C7 and V5C1, as well as their respective point mutants, recognized indistinguishable epitopes on RTA, at least at the level of sensitivity afforded by hydrogen‐deuterium mass spectrometry. The results of this study have implications for engineering therapeutic antibodies because they demonstrate that even subtle differences in epitope specificity can account for important differences in antibody function.